A pilot randomized controlled trial of a post‐discharge program to support emerging adults with type 1 diabetes mellitus transition from pediatric to adult care. Issue 8 (11th November 2014) - Steinbeck, Katharine S; Shrewsbury, Vanessa A; Harvey, Vanessa; Mikler, Kara; Donaghue, Kim C; Craig, Maria E; Woodhead, Helen J
Abstract : Aims: There is a paucity of randomized controlled trials (RCT) examining transition from pediatric to adult care in type 1 diabetes mellitus (T1DM). This study aimed to determine if transition in T1DM is more effective with a comprehensive transition program (CTP) compared with standard clinical practice (SCP). Methods: This RCT recruited as young people left pediatric diabetes services. The trial co‐ordinator provided CTP participants with standardized telephone communication support at week 1, and 3, 6, and 12 months post‐discharge from pediatric care. SCP participants were briefly contacted at 6 and 12 months post‐discharge to confirm transfer status; they received no other post‐discharge contact as per usual practice. At 12 months, the primary outcomes were engagement and retention in the adult service and secondary outcomes included hemoglobin A1c (HbA1c), diabetes‐related hospitalizations, microvascular complication appearance, and global self‐worth. Results: Most CTP participants (11/14) and all SCP (12/12) participants (P = 0.2) transferred to an adult diabetes service; the median time to transfer was 14–15 wk. Overall, participants' frequency of adult diabetes service visits was sub‐optimal but their retention in adult care was high. The only group difference was a higher HbA1c at baseline and follow‐up in the CTP group. However, a general linear model found that follow‐up HbA1c increased by 1.2% for each percentage increase in baseline HbA1c [95% confidence interval (0.4, 1.9; P = 0.01)], independent of treatment group. Conclusions: Despite the challenges in recruiting adequate numbers, these findings provide valuable insights for future T1DM transition RCTs that are needed to build a more solid evidence‐base in this field.